Pyrolysis characteristics and kinetic studies of horse manure using thermogravimetric analysis - Chong, Cheng Tung; Mong, Guo Ren; Ng, Jo Han; Chong, William Woei Fong; Ani, Farid Nasir; Lam, Su Shiung; Ong, Hwai Chyuan (Elsevier, 2019)
Horse manure is a biowaste with bioenergy recovery potential for heat and power generation. However, there is no kinetics data in literature to date. In this work, a kinetic study of the pyrolysis process of horse manure is investigated through the use of thermogravimetric analyses. The samples were heated over a range of temperature from 298 to 927 K with four different heating rates of 1, 2, 5 and 10 K/min. The weight loss was measured by a thermogravimetric analyser in an inert atmosphere. The differential thermal gravimetric (DTG) thermogram shows that the highest reaction rate occurred at between 290.2 and 329.6 °C where the devolatilisation process was initiated to overcome the activation energy barrier of the manure. The activation energy and pre-exponential factor obtained by the Kissinger method, assumed to be constant throughout the whole pyrolysis process are 149 kJ/mol and 3.3 × 1012 s−1, respectively. The activation energy calculated from the non-isothermal Flynn-Wall-Ozawa (FWO), Kissinger-Akahira-Sunose (KAS) and Friedman methods are 199.3, 200.2 and 194.6 kJ/mol, whereas the pre-exponential values are 9.3 × 1018, 1.8 × 1019 and 3.6 × 1020 s−1, respectively. The kinetic parameters determined based on interval conversional fraction shows good agreement. The high volatile and low ash content in horse manure indicates the potential for bioenergy recovery. The results of the kinetic study can be used for modelling devolatilisation and designing thermochemical conversion processes.